Prevalence and Financial Significance of Bovine Fasciolosis in Oda-Bultum District, West Hararge, Oromia Regional State, Ethiopia - Kebede Ayele Terefe (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
A study was conducted from November 2010 to February 2011 to determine the prevalence and estimate the economic loss of bovine fasciolosis in OdaBultum district based on the carpological examination and abattoir survey. Out of total of 384 fecal samples taken from cattle and examined, 182 (47.39%) were found positive for fasciolosis ,prevalence on months basis revealed higher prevalence rate (48.78%) in January and the lower (43.47%) was observed in November. No statistically significant variation (p>0.05) was observed in the monthly occurrence of the disease. Among the three localities (Godahora, Odaroba and Odabiyyo) from which fecal samples were taken higher infection rate (48.75%) was recorded in Odabiyyo while the lowest (46.27%) was noted at Odaroba. Statistical analysis of the result revealed no significant differences in prevalence among the three localities. Prevalence among the age groups showed 48.32% and 46.75% in young and adult age groups, respectively. No statistically significant difference in prevalence was seen between the two age group (p>0.05). Prevalence on the basis of sexes indicated 50% in male and 45.53 in females but the difference was not statistically significant (p>0.05). A four month post mortem examination of 197 cattle slaughtered at baddessa town municipal abattoir revealed the overall prevalence of 47.68%. Statistical analysis showed that there was no significant variation in monthly prevalence during the study period (p>0.05). Analysis of economic losses associated with liver condemnation in the study abattoir indicated a total of 13,498 ETB has been estimated to be lost each year in the abattoir as a result of fasciolosis. The current study has indicated that disease is of considerable economic significance therefore, calls for implementation of an appropriate control measures.